Prevention of Preeclampsia with Aspirin in Multiple Gestations: A Systematic Review and Meta-analysis - Bergeron, Tessa S.; Roberge, Stéphanie; Carpentier, Caroline; Sibai, Baha; McCaw-Binns, Affette; Bujold, Emmanuel (American Journal of Perinatology, 2016)
Objective The objective of this study was to estimate the effect of low-dose aspirin in multiple gestations to prevent preeclampsia and small for gestational age (SGA) neonates.Methods A systematic review and meta-analysis were performed through electronic database searches. Randomized controlled trials (RCTs) of women with multiple gestations assigned to receive aspirin or placebo or no treatment were included. Outcomes included preeclampsia (mild and severe) and SGA neonates. Relative risks (RR) with their 95% confidence intervals (CI) were calculated.Result Out of 6,853 citations, 6 RCTS, including 898 pregnancies, were included. We observed a significant reduction in the risk of preeclampsia (RR, 0.67; 95% CI, 0.48–0.94) and mild preeclampsia (RR, 0.44; 95% CI, 0.24–0.82) but not severe preeclampsia (RR, 1.02; 95% CI, 0.61–1.72) with low-dose aspirin. The risk of SGA was not changed (RR, 1.09; 95% CI, 0.80–1.47). The reduction of preeclampsia was not different between women randomized before (RR, 0.86; 95% CI, 0.41–1.81) or after 16 weeks' gestation (RR, 0.64; 95% CI, 0.43–0.96) (p = 0.50).Conclusion There is low level of evidence supporting the use of low-dose aspirin for the prevention of preeclampsia and SGA neonates in multiple gestations.
Keywords: pregnancy; preeclampsia; multiple gestation; twin; aspirin